Increased Public Understanding of the Agreement on Fish Management in Sungai Paku Village Kampar Kiri Sub-District Kampar District - Yeni Triana (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2021)
The purpose of this service to the community is to analyze the implementation of the contents of the agreement agreed on by both parties in Sungai Paku Village, Kampar Kiri Subdistrict, Kampar Regency, in the aspect of legal consequences caused not to implement the agreement of default, in the perspective of business law. The target of the settlement of this defaulting case is very important in the business world for business competition to improve the standard of living of the Sungai Paku Village community, in particular and, hence the follow-up of the results of this service, may be useful for the service team and outside parties related to small and medium enterprises regarding this default is in the form of material articles on lecture studies for students and allows at the same time to do community service. The method of implementation is sociological law research which is more focused on the problems that arise and for that the researcher focuses on the discussion of statutory provisions and see how law is practiced in society. In the discussion of service found that the problems faced by the community, it is necessary to solve the problem by providing a clear picture to the community.